Human hepatocyte--a model for toxicological studies. Functional and biochemical characterization - Modrianský, M; Ulrichová, J; Bachleda, P; Anzenbacher, P; Anzenbacherová, E; Walterová, D; Simánek, V (General physiology and biophysics, 2000)
Isolated human hepatocytes (HH) are an accepted model for in vitro experiments for testing liver function and xenobiotic metabolism. Preferred over more traditional animal hepatocyte model used in toxicological studies, it is the model of choice when substances undergoing biotransformation in man are investigated. The aim of this study was to optimize isolation and culture conditions for HH primary culture with regard to cell yield, viability, and metabolic activity, and to evaluate the suitability of donor samples for toxicology experiments. Cell viability, total cytochrome P450 (CYP) content, CYP3A4, CYP1A2 activity, and finally mixed ethoxycoumarin-O-deethylase (ECOD) activity were parameters measured in order to characterize the isolated HH. The quality of the primary cultures, stable and functional for a seven-day period following 24 hour stabilization, was assessed by lactate dehydrogenase (LDH) leakage and response to the model toxin tert-butylhydroperoxide (tBH) and to silybinin, a model cytoprotective substance. Based on HH obtained from livers of five multiorgan donors (average age 44.8 years, three males and two females), the individual variability of donors needs to be considered in evaluating cultures focussing on clinical liver tests. Greater sensitivity to toxins and silybinin was found in the hepatocyte culture from one donor with higher aminotransferase activity. In another case, higher serum bilirubin appeared to be linked to higher ECOD activity. Our conclusion is that values of clinical liver tests ought to suggest a healthy organ thus eliminating previous hepatocyte damage, the crucial factor of primary culture stability and functioning.
Keywords: 7-Alkoxycoumarin O-Dealkylase; Liver; Microsomes, Liver; kultivované buňky; Hepatocytes; tert-Butylhydroperoxide; játra; systém (enzymů) cytochromů P-450; testy toxicity; Calcium Channel Blockers; Antioxidants; oxygenasy se smíšenou funkcí; Cell Culture Techniques; Cytochrome P-450 CYP3A; Time Factors; rifampin; Middle Aged; mužské pohlaví; silymarin; L-laktátdehydrogenasa; Adult; Cytochrome P-450 Enzyme System; Mixed Function Oxygenases; Silymarin; antioxidancia; blokátory kalciových kanálů; cytochrom P-450 CYP1A2; hepatocyty; Cells, Cultured; nifedipin; ženské pohlaví; Cytochrome P-450 CYP1A2; 7-alkoxykumarin-O-dealkylasa; terc-butylhydroperoxid; Humans; Rifampin; L-Lactate Dehydrogenase; časové faktory; lidé středního věku; buněčné kultury; jaterní mikrozomy; Nifedipine; dospělí; Female; cytochrom P-450 CYP3A; Toxicity Tests; Enzyme Inhibitors; lidé; Male; inhibitory enzymů